Development of Light-Responsive Poly(γ-Benzyl-L-Glutamate) as Photo Switches by a One-Step NCA Method - Chen, Pin; Kong, Jingyang; Wang, Xin; Ma, Weiye; Yang, Xia; Qin, Yuqing; Hu, Xiaohong (Frontiers in Chemistry, 2020)
Synthesized polypeptide attracted increasing interests due to their excellent biological characteristic and adjustable chemical properties in bio-related field. But polypeptide itself had no switching properties, which would beneficial its application as a control component. Herein, light responsive poly(γ-benzyl-L-glutamate)s (PBLGs) was synthesized by one-step NCA method using p-aminoazobenzene (m-AZO) and p-diaminoazobenzene (m-DAZO) as initiators. PBLGs exhibited amorphous characteristic with obvious Tg transition, which was 14 0C for PBLG1 and 21 0C for PBLG2. In order to forecast structure-property information of PBLGs, theorical UV-vis spectra as well as the energy gap between HOMO and LUMO was calculated by DFT calculation. Experimental results of UV-vis spectra exhibited similar characteristic to that of theorical UV-vis spectra except 40-50 nm red-shifting of absorbance peak. Furthermore, absorbance intensity of PBLGs had good linear relationship to their concentration, but their linearity range depend on concentration was completely different. Then, trans cis transition under different excitation source and cis trans recovery in dark environment were real-timely tracked to evaluate its light response performance by UV-vis spectra. It was found that UV light was only effective excitation source for PBLG1 and blue light was another effective excitation source for PBLG2 besides UV light. Furthermore, addition of alcohol and water as cosolvent had little effect on trans cis transition in UV light excited system, but it shortened recovery time of cis trans process in dark environment. Differently, the detectable isomerization process become unclear with the addition of alcohol in blue light excited system. Further, either alcohol or water in solvent would accelerate both trans→cis process and cis→trans process in blue light excited system.